2019
DOI: 10.1097/ccm.0000000000003912
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Rapid Response Calls in the United States: An Analysis of the First 402,023 Adult Cases From the Get With the Guidelines Resuscitation-Medical Emergency Team Registry

Abstract: Objectives: To characterize the rapid response team activations, and the patients receiving them, in the American Heart Association-sponsored Get With The Guidelines Resuscitation-Medical Emergency Team cohort between 2005 and 2015. Design: Retrospective multicenter cohort study. Setting: Three hundred sixty U.S. hospitals. Patients: Consecutive adult patients ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
39
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 20 publications
4
39
0
1
Order By: Relevance
“…Among the subjects in this study, 70.4% had been hospitalized in the medical department, which was a result similar to that reported in previous studies [ 11 , 15 ], but the proportions of subjects with solid cancer and hematological malignancy were high, at 39% and 9.5%, respectively, accounting for approximately half of all subjects (47.9%). However, the proportion of subjects with DNR discussion was 10.6%, and the ICU transfer rate was 29.5%, which were not higher than those reported in other studies [ 16 , 17 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Among the subjects in this study, 70.4% had been hospitalized in the medical department, which was a result similar to that reported in previous studies [ 11 , 15 ], but the proportions of subjects with solid cancer and hematological malignancy were high, at 39% and 9.5%, respectively, accounting for approximately half of all subjects (47.9%). However, the proportion of subjects with DNR discussion was 10.6%, and the ICU transfer rate was 29.5%, which were not higher than those reported in other studies [ 16 , 17 ].…”
Section: Discussionsupporting
confidence: 90%
“…However, the cohort in this study shows higher intervention rates when comparing by item. In the large-scale study by Lyons et al that included 151,400 cases of RRT activation in major hospitals in the United States, the rate for intubation was 4.6% (vs. 13.3% in the cohort of this study), bedside ultrasonography was 0.3% (vs. 13% in the cohort of this study), and newly started antibiotics was 1.5% (vs. 6.6% in the cohort of this study), which were lower than those in this study [ 11 ]. In the study by Chan et al published in 2008, the rate of intubation was 7.4% (vs. 13.3% in the cohort of this study), arterial line insertion was 0.8% (vs. 17.9% in the cohort of this study), and intravenous vasopressor administration was 1.3% (vs. 12.9% in the cohort of this study), which showed lower intervention rates than those reported in this study [ 12 ].…”
Section: Discussionmentioning
confidence: 64%
“…Hospitalwide medical emergency triggers based on USA data include cardiovascular 37.4%, respiratory 38%, neurological 30.7%. 8 The standard day procedure working hours at our institution are 08:00 to 17:00. Nine MER call and three CB events occurred outside of standard day procedure working hours, representing 25.5% of MER/CB events in the unit, and 1.63% of all events in the hospital.…”
Section: Discussionmentioning
confidence: 99%
“…System activations from staff members who are concerned or 'worried' about the patient account for 14-25% of activations. 8,11 Post-operative hypotension was the single most common RDR parameter (n=16). With the exception of the case involving a septoplasty and turbinate reduction, all other cases were managed on the ward with intravenous fluids ± further investigations such as bloods and ECG without transfer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation